Cancer immunotherapy clinical trials to support urgently needed access in low- and middle-income countries: a report from the SITC global access and impact committee - T Peter Kingham; Innocent Adoubi; Avery D Posey; Ahmad A Tarhini; David R Kaufman; Jyoti Bajpai; Solmaz Sahebjam; Mauricio Burotto; Verna Vanderpuye; Thomas S Uldrick; Olufunmilayo I Olopade; Thomas A Odeny; et al. (Journal for ImmunoTherapy of Cancer)
Cancer is rapidly on the rise as a cause of morbidity and mortality in low- and middle-income countries (LMICs). However, despite the increasing importance of immune checkpoint inhibitors (ICIs) as a pillar of cancer therapy, access in these settings lags well behind that in high-income countries (HICs). Increasing the evaluation of ICIs through local clinical trials and demonstration projects, and inclusion in multinational clinical trials is the first step to improving access. In particular, the epidemiology and clinical presentation of cancer in LMICs is often distinct from that in HICs, and the impact of immune checkpoint blockade in these settings is understudied. Moreover, unique patterns of comorbidities, environmental factors, genetic diversity, and paucity of supportive infrastructure may all impact the risk-benefit and outcomes of cancer immunotherapy treatment. Local clinical trials not only directly impact the strengthening of infrastructure but also provide local authorities with better insight into the health economic benefit of cancer immunotherapy, giving impetus to adoption and reimbursement efforts. More local, regional, and multinational collaborative efforts are needed to speed up the evaluation, access, and adoption of ICIs throughout the developing world.